BELGRADE STOCK EXCHANGE INDICES IN THE CONDITIONS OF THE COVID-19 PANDEMIC - Đekić, Marija; Vesić, Tamara; Šormaz, Goran (Ekonomija - teorija i praksa, 2022)
The paper aims to present the movement of the Belgrade Stock Exchange index from the beginning of the epidemic in the Republic of Serbia until the middle of 2021, as well as a review of the movement of the most important indices in the world. The global crisis, caused by the spread of the virus, but also by rigorous measures introduced by the entities authorized by the Government, resulted in a decline in general economic activity, economic slowdown in the capital market and, consequently, a decline in stock indices in the world and in our country. The results of the research indicate that, in general, the indices show drastic declines as early as the beginning of 2020, and although they ended the year with a positive trend, most of them have not yet recovered. The indices of the Belgrade Stock Exchange, already weak, despite a certain degree of recovery during the second half of 2020, had a negative trend compared to the year before. It is completely unknown how long the pandemic and the crisis will last, so it is difficult to predict the further course of events, but it is certain that the consequences will be felt for a longer period of time in economic flows, primarily through increased inflation and further deterioration of public finances.